THE EFFECT OF BUDGET REFOCUSING IN THE TIME OF COVID-19 FOR EMPLOYEE BENEFITS 2020-2021 IN BKPSDM BADUNG REGENCY - S. Yuki, Hanako Regina; Widhi Antari, Ni Putu Bayu (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
As one of the Regional Governments whose regions have determined COVID-19, the Bali Provincial Government in this case the Badung Regency Government Center (PUSPEM BADUNG) in the Department of Personnel and Human Resources Development, in 2020-2021 will make efforts to find budget problems. that happened. The issue raised is the Effect of Budget Refocusing for 2020-2021 on Employee Allowances and the inhibiting factors experienced by the Personnel and Human Resources Development Agency in carrying out budget refocusing or budget allocation for employee benefits. Where Budget Refocusing is the reallocation of the refocusing activity budget to be allocated to activities that were not previously allocated through a budget change mechanism by activating/moving/lowering the budget from previous activities to other activities. Meanwhile, Employee Allowances are in addition (in various forms) beyond the salary provided by the company to employees to increase income. The results of this study indicate that in 2020-2021 there will be a decrease in Additional Employee Income (TPP) by 50% due to the absence of regional income. Therefore, the implementation of budget refocusing on Employee Allowances is intended as a form of economic support (budget) by refocusing a budget and also other options so that with the enactment of this budget allocation, employee allowances can be realized.